ROBERT BURNS’ PATRIARCHIC RESPONSE TO WIFE’S DOMINANCE OVER HUSBAND IN HIS POEM, THE HENPECKED HUSBAND (1788) - Reza Noviana Cahyani; Heri Dwi Santoso; Yunita Nugraheni (Dinamika Bahasa dan Budaya, 2019)
The Henpecked Husband is one of classic poems written by Robert Burns, a neoclassical poet. This poem overall tells about a man who lives under the dominance of his wife. It also contains the some (parts of) lines that represent his opinions about the situation, which tends to blame the couple for the situation. Given the author’s tendency in the writing a research was conducted, aimed at comprehending in detail the manifestations of woman’s (wife’) dominance over the husband in the poem and analyzing and classifying the poet’s opinions theory. To do this library research, gender feminist theory was employed, with primarily feminist concepts written by Rosemary Putnam Tong. Based on the research, there were some major findings. Firstly, there were some manifestations of wife’s dominance over the husband, i.e. in power relation, leadership, decision making, and family’s economy. Secondly, there were some expressions (lines) in the poem that showed the poet’s patriarchal response towards such dominances. Keywords: patriarchal, wife’s dominance, gender, gender feminism